З ІСТОРІЇ САМОВРЯДУВАННЯ В УКРАЇНСЬКОМУ СЕЛІ В 1920-ті РОКИ (Zaporizhzhia Historical Review, 2021)
The article deals witch the attempts to compare the work of a village gathering, land society and village council in the Ukrainian village in the 1920-s.